Visible light induced photocatalytic degradation of norfloxacin using xC-TiO2 - Adnan; Kalsoom; Farah Muhammad Zada; Sarwat; Ho Soonmin; Behramand Khan; Muhammad Alamzeb; Wei Sun; Jawad Ikram; Najeeb ur Rehman (Heliyon)
In recent years, antibiotic pollution has become a major environmental concern. The extensive production and widespread use of prescribed antibiotics have significantly impacted ecosystems. The main objective of the present study is to investigate the photocatalytic degradation of the antibiotic norfloxacin (NFX) under visible light. In this work photocatalysis of NFX was demonstrated under the source of visible radiation by using carbon dopped-titania (C-TiO2) nanoparticles as catalyst prepared by a modified sol-gel method using n-hexane and benzene as carbon precursors. The synthesized samples were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), and energy dispersive X-ray (EDX) techniques. The effect of various parameters like initial concentration, catalyst dosage, irradiation time, pH, and inorganic ions were investigated on the photocatalysis of NFX. The XRD and SEM analysis exhibits that the synthesized C-TiO2 nanoparticles were of anatase phase having spherical shape with a mean particle size of about 11–17 nm. The results shows that the best photocatalytic efficiency (74 % & 81 %) was achieved at pH = 8 in 150 min. The degradation of NFX follows pseudo-2nd -order kinetics, while favors Langmuir isotherm model. The inhibition effect of various inorganic ions on the photocatalysis of NFX was in the order of F⁻>SO42⁻>HCO3⁻>NO3⁻. The present study shows that C-TiO2 is an optimistic and efficient catalyst for the photocatalysis of NFX antibiotics.